Data science based landscape ecology for traditional village landscape protection. (19th June 2021) - Liu, Tong; Wang, Shijun; Wang, Zi; Li, Bingxin; Guo, Sulin; Wei, Baowei
With the revitalisation of rural areas and the advancement of new rural construction, at present, the traditional village protection has received more attention. The optimisation of village layout is an essential issue in the protection of traditional villages, which is not only an objective demand for rural development, but also an important way to protect and avoid damage to the ecological and landscape patterns of the original villages. With the increase in the development of traditional villages, the general scale and shape of traditional villages have found profound changes. The phenomenon of village landscape convergence and original landscape destruction occurs from time to time. In the new situation, the traditional village protection faces new opportunities and challenges. By using landscape ecology theory to guide the preservation of traditional villages, the integrity, authenticity and continuity of traditional villages can be maintained. This article takes Yueqing Town, Bailong Village and Shixian Town, Shuinan Village in Yanbian Prefecture, Jilin Province as the research objects, applying the landscape pattern index to quantitatively analyse its overall landscape. On this basis, the village landscape optimisation and preservation strategy is proposed, which has certain reference value for the preservation and reuse of traditional villages in Jilin Province.